2014
DOI: 10.1007/s10531-014-0698-2
|View full text |Cite
|
Sign up to set email alerts
|

Orchid (Orchidaceae) decline in the Catoctin Mountains, Frederick County, Maryland as documented by a long-term dataset

Abstract: A 41-year study of the orchids of the Catoctin Mountains, Frederick County, Maryland reveals that 19 of 21 species have experienced precipitous declines. Four of these species are currently considered Threatened or Endangered by the State of Maryland and another two are considered Rare. Annual census data at 167 sites from throughout the Catoctin Mountains on protected and unprotected lands (private and public) show a loss of three species from the study area, a decline of[90 % (ranging from 99 to 91 %) in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Our data provide clear evidence that efforts to reduce deer abundance and impact are needed to safeguard the more palatable and/or less browse-resistant species that continue to suffer at present deer densities ( Knapp and Wiegand 2014 ). All our sites at West Point allow access by recreational hunters, but that did not prevent high deer browse rates of oak seedlings.…”
Section: Discussionmentioning
confidence: 85%
“…Our data provide clear evidence that efforts to reduce deer abundance and impact are needed to safeguard the more palatable and/or less browse-resistant species that continue to suffer at present deer densities ( Knapp and Wiegand 2014 ). All our sites at West Point allow access by recreational hunters, but that did not prevent high deer browse rates of oak seedlings.…”
Section: Discussionmentioning
confidence: 85%
“…However, management whose only goal is to increase light levels may not be the most appropriate strategy because several factors may interact to influence plants’ performance. Dibble et al [ 20 ] found that increased canopy openness resulted in the increased growth of plants, especially ferns, that would compete with Isotria and increased herbivory that has been shown to have a negative impact on native orchids [ 9 , 52 ]. The increased competition was not a problem at our study sites because few other herbs were present and none that were there were dense enough or high enough to interfere with Isotria .…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern US, fire suppression in forests has had a major impact on the characteristics of plant communities [ 8 ]. In some instances, orchid populations are threatened by the increased abundance of native species, especially herbivores [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change could impact both their fungal partners and pollinators, with mismatches in phenology becoming more likely (Robbirt, Roberts, Hutchings, & Davy, 2014). Increases in deer populations and wintering grounds (from changes in snowpack) could reduce reproduction and survival (Knapp & Wiegand, 2014). Demographic modeling provides an avenue to understand which aspects of the life cycle most impact population growth currently and which may be most vulnerable to future change.…”
Section: Introductionmentioning
confidence: 99%